Analysis of Students' Mathematical Problem-Solving Abilities on Systems of Linear Equations in Two Variables - Ananda Dewi Safitri; Westi Bilda; Prawidi Wisnu Subroto (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2026)
Mathematical problem-solving ability is one of the essential competencies in mathematics learning, particularly in the topic of Systems of Linear Equations in Two Variables (SPLDV). However, many students still experience difficulties in understanding word problems, determining variables, constructing mathematical models, carrying out solution procedures, and checking the final results. This study aimed to analyze students’ mathematical problem-solving ability in SPLDV material based on Polya’s stages, namely understanding the problem, devising a plan, carrying out the plan, and looking back. This study employed a qualitative method with a descriptive approach. The research subjects were six students of class VIII F at SMP Negeri 5 Kota Tangerang, selected purposively to represent high, medium, and low ability categories. Data were collected through essay tests and interviews, and then analyzed based on the indicators of mathematical problem-solving ability at each stage of Polya’s problem-solving process. The results showed that students in the high category were able to solve problems systematically at all stages. Students in the medium category were able to understand the problem and devise a plan, but still made errors in carrying out the plan. Meanwhile, students in the low category experienced difficulties in almost all stages of problem solving. In general, the most difficult stages for students were carrying out the plan and looking back at the results. This study concludes that students’ mathematical problem-solving ability in SPLDV varies according to their ability level, with major weaknesses in the implementation and checking stages. The findings imply that mathematics instruction should place greater emphasis on modeling practice, procedural accuracy, and reflective checking of solutions.